2021
DOI: 10.33196/zoer202102052301
|View full text |Cite
|
Sign up to set email alerts
|

Raising the Bar: The Development of Docket Control on the Court of Justice

Abstract: We examine the emergence and evolution of docket control mechanisms in the preliminary ruling procedure. Using both legal and statistical analysis, we show that reasoned orders have increased dramatically since the mid-1990s, with courts in Italy and Central and Eastern member states being the most frequent targets. We argue that the trajectory of the European Court of Justice's docket policy is an indirect manifestation of its ascendant position as Europe's judicial powerhouse. Facing a rising caseload, the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Dyevre et al, for example, found that the Court's increasing practice of using reasoned orders is a strategic way of controlling its docket. 71 Similar views have been expressed by Advocate General Bobek, who questioned the need of having all preliminary questions referred to the ECJ over worries how the Court's workload may affect the quality and efficiency of justice. 72 These interviewees are well aware of the formal rules whereby courts of final instance are obliged to refer questions regarding the interpretation of EU law while lower courts may do so if they want to.…”
Section: B Passive For Different Reasonsmentioning
confidence: 78%
“…Dyevre et al, for example, found that the Court's increasing practice of using reasoned orders is a strategic way of controlling its docket. 71 Similar views have been expressed by Advocate General Bobek, who questioned the need of having all preliminary questions referred to the ECJ over worries how the Court's workload may affect the quality and efficiency of justice. 72 These interviewees are well aware of the formal rules whereby courts of final instance are obliged to refer questions regarding the interpretation of EU law while lower courts may do so if they want to.…”
Section: B Passive For Different Reasonsmentioning
confidence: 78%
“…The most comprehensive empirical treatment of the CJEU's use of orders so far is that by Dyevre et al . (2021). See also Dyevre et al ., 2022).…”
Section: Empirical Analysis Of the Use Of Ordersmentioning
confidence: 99%
“…See also Dyevre et al ., 2022). They argue that the Court has become more restricted over time – as the supply of references has grown – in terms of which questions they afford with a judgment, and that orders have increasingly been used as ‘a type of resource management mechanism’ (Dyevre et al ., 2021, p. 564). They also demonstrate a systematic statistical relationship between the proportion of preliminary references ending in an order and the number of cases waiting on the Court's docket.…”
Section: Empirical Analysis Of the Use Of Ordersmentioning
confidence: 99%
See 1 more Smart Citation